An exploratory analysis of ecological water requirements of macroinvertebrates in the Wuhan branch of the Yangtze River. (4th September 2015) - Pan, Bao-Zhu; Wang, Hong-Zhu; Ban, Xuan; Yin, Xin-An
Abstract: The natural flow regime is confirmed to be the main driving factor in maintaining diverse species and abundant production of river floodplains. However, disturbance of human activities have affected natural hydro-geomorphical process, reduced habitat heterogeneity, and weakened ecological service functions. Thus, it is necessary to assess ecological water requirements and furthermore provide a quantitative operational basis for restoring natural flow regime. Macroinvertebrates are considered as good indicators of hydrological regime changes due to their confinement to the bottom, limited abilities of movement, and low tolerance. This paper deals with systematic ecological investigations in the Wuhan branch of the Yangtze River during 2007–2008. Altogether, 32 taxa of macroinvertebrates belonging to 13 families and 27 genera were identified. The density and biomass of total macroinvertebrates were 181 ind m −2 and 0.29 g dry mass m −2, respectively. Canonical Correspondence Analysis (CCA) revealed that the important environmental factors influencing macroinvertebrate abundance were flow velocity (U), water depth (Z), and total nitrogen (TN). The relation between habitat weighted usable area and water discharge was analyzed on basis of creating suitability curves. Weighted usable area of habitat showed unimodal changes with increasing water discharge, i.e., first increased and then decreased, and weighted usable area of habitat reached the maximum when flow discharge was 21, 000 m 3  s −1 .